Works In Primary School Textbooks and The Impact of Their Content on The Formation of Student Consciousness - Anvarova Shohsanam A’zamjon qizi (Zien Journals, 2022)
This article discusses the works in the primary school textbook, the features of anthroponomy in them, and the problems and solutions to the impact of these names on the minds of students
Keywords: immunity; innovative education; modernization; methodology